Respuesta :
(X/3 - 2) + (X/2 + 6) = 3
X/3 - 2 + X/2 + 6 =3
5X/6 + 4 = 3
5X/6 = 3 - 4
5X/6 = - 1
5X = - 1 times 6
5X = - 6
X = - 6/5
And in decimal form: - 1.2
X/3 - 2 + X/2 + 6 =3
5X/6 + 4 = 3
5X/6 = 3 - 4
5X/6 = - 1
5X = - 1 times 6
5X = - 6
X = - 6/5
And in decimal form: - 1.2
Answer:
x=−6/5
Step-by-step explanation:
[tex]\frac{x}{3} - 2 + \frac{x}{2} + 6 = 3\\[/tex]
Simplify both sides of the equation:
[tex]\frac{x}{3} - 2 + \frac{x}{2} + 6 = 3[/tex]
[tex]\frac{1}{3} x + -2 + \frac{1}{2} x + 6 = 3[/tex]
[tex]( 1/3x + 1/2x ) + ( −2+6 ) = 3[/tex] (Combine Like Terms)
[tex]5/6 x + 4 = 3[/tex]
Subtract 4 from both sides:
[tex]5/6x + 4−4= 3−4[/tex]
[tex]5/6x = −1[/tex]
Multiply both sides by 6/5:
[tex](6/5) * (5/6x) = (6/5) * (−1)[/tex]
[tex]x=−6/5[/tex]